Pengaruh Penggunaan Celebrity Endorser Cristiano Ronaldo sebagai Model Iklan terhadap Brand Image Shopee - Juniardi, Fajar; Sekartaji, Sekartaji (PROPAGANDA, 2024)
In advertising there are many strategies in building an image, one of which is the use of celebrity endorsers. The purpose of this study was to determine the effect of using celebrity endorser Cristiano Ronaldo as an advertising model on Shopee brand image. Shopee is an e-commerce site that was founded in 2015. E-Commerce is a business transaction that takes place using an electronic network system such as the internet. To be accepted among the Indonesian people, Shopee runs a C2C (customer to customer) mobile marketplace business. The method used is to conduct a survey that will be given to Shopee users who have seen Cristiano Ronaldo's advertisement as a Shopee celebrity endorser. This research design has a purpose to find the influence between two variables, namely the variable (X) is a celebrity endorser while the variable (Y) is the brand image. Respondents who were involved in this study were Shopee users with male or female criteria and aged 16-30 years who lived in Jabodetabek. Sampling in this study was conducted in a non-probability way. Using the purposive method with a sample of 100 respondents. The results of the research that has been carried out with validity and reliability tests are valid and reliable, and according to the calculation of simple linear regression analysis, it can be seen that Celebrity endorser (X) has a significant effect on Brand Image (Y). From this test, it can also be seen that Celebrity Endorser has a coefficient of determination between Brand Image of 70.8%, Celebrity Endorser variable affects Brand Image. From the results of this study, it can be concluded that Celebrity Endorser (X) has a very strong influence on Brand Image (Y).